VIRTUAL PRINTING STUDIOS FOR ART STUDENTS - Sharma, Aakash; Shahare, Devendra Y.; Das, Debayan; Poonguzhali S; Neha; Gadave, Shweta Ishwar (ShodhKosh: Journal of Visual and Performing Arts, 2025)
Virtual Printing Studios are a disruptive model of teaching printmaking in which digital simulation, artificial intelligence, and immersive technologies are brought into the conventional artistic processes. This paper suggests and tests a detailed Virtual Printing Studio model that is specific to the art students, and allows them to experience learning virtually, not being limited by physical studios, materials, and time. It is based on a digital representation of core printmaking methods - relief, intaglio, lithography, and screen printing - and offers virtual means of manipulation of inks, plates, textures and substrates at high fidelity of visual and procedural output. Smart components operated with AI improve the learning process with the help of intelligent design aids, layout optimization, and real-time simulation of printing pressure, layering effects, and material behavior. Error-detection and print preview correction can be automated to enable iterative experimentation, which removes waste of materials and reduces the risks of injuries that students can experiment with creative variations without posing risks to safety. Mixed-method research methodology was used, which is a combination of experimental comparisons with traditional print studios, student performance measures, surveys, and portfolio-based measurements. The findings indicate that students who studied in Virtual Printing Studios displayed better conceptual knowledge of print processes, were more creative in experimentation and were more engaged than students who studied in traditional environments. The immediate feedback and repeatable simulation were used to accelerate the acquisition of the skills whereas the accessibility was widened to include institutions with infrastructural or resource constraints. In spite of the issues associated with the gap in realism, the digital literacy needs, and hardware reliance, the results indicate high pedagogical benefits of hybrid and fully virtual printmaking education.